Penerapan Model Pembelajaran Berbasis Masalah Untuk Meningkatkan Aktivitas Dan Hasil Belajar Siswa - Ni Luh Suartini (Jayapangus Press, 2020)
This study aims to improve the activities and student learning outcomes of Class IX-G SMP Negeri 5 Amlapura Semester I Academic Year 2018/2019. The subjects in this study were 22 st grade students, amounting to 22 people; consisting of 8 male students; and 14 female students, in the first semester of the 2018/2019 school year. This study uses a class action research design through two stages. Student learning activity data is collected by observation sheets, and learning outcome data is collected by multiple choice tests. Both types of data were analyzed by quantitative descriptive methods. Before the two stages are carried out, the initial observation activities are conducted by the students' learning activities, and analyzing the questions of UTS Indonesian Language Class IX semester I of academic year 2018/2019. The activity was carried out to determine the level of initial activity and student learning outcomes before the implementation of the Problem Based Learning model. The results of this study indicate that the application of the Problem Based Learning design can increase learning activities and Indonesian language learning outcomes of Class IX-G SMP Negeri 5 Amlapura semester I of 2018/2019, namely in the initial observation of low student learning activities, increasing from an average of 59,77 and completeness 13,63% in the first stage, in the second stage the average student learning activity was 81.25 and the completeness level was 86,36%. While student learning outcomes increased from an average of 68,18, absorbency of 68,18%, and classical completeness level of 50,00% at initial reflection, increased to an average of 69,09, absorptive capacity of 69,09%, and the level classical completeness was 59,09% in stage I. In stage II it increased to an average of 77,27, absorbency 77,27%, and classical completeness rate 90,91%. Based on these results the researchers formulated suggestions; (1) Students are expected to be able to utilize this Learning design to improve their learning activities and outcomes; (2) Other teachers can apply this learning design, by examining the weaknesses of the results of this study; (3) Schools can make consideration material as one of the learning design that can be developed to solve learning problems in class; (4) Other researchers can make the results of this study a relevant research study.